G Protein-Coupled Receptors. - Shukla, Arun K. (Methods in cell biology ;, 2017)
"The largest family of cell surface receptors in our body, referred to as G protein-coupled receptors, plays central roles in the onset and regulation of many different physiological processes. The cascade starts with binding of the "stimulus" (i.e., an activating ligand; agonist) to its cognate GPCR, followed by receptor activation, effector coupling and initiation of downstream signaling responses. Subsequently, the receptors are internalized as a mechanism of blunting the signaling response arising from the surface. Afterwards, the receptors are either recycled back to the plasma membrane to get ready for a new signaling cycle, or degraded via proteosomal and lysosomal mechanisms. In the latter case, newly synthesized receptors occupy the membrane, thus making the cell receptive again for the incoming stimulus. Development of precise and sensitive methods to measure the activation and signaling responses of GPCRs has been at the center stage of GPCR research. As a result, a number of assays have been designed, validated, and utilized to assess the ligand binding, effector coupling and receptor trafficking in cellular context. In addition, several approaches have also been developed and optimized to study ligand?receptor and receptor?effector interactions in vitro. Furthermore, direct computational approaches guided by the recent surge of structural data on GPCRs are also being developed rapidly to better understand the conformational dynamics and effector interactions of GPCRs. In this volume of Methods in Cell Biology entitled "Measuring GPCR Activation and Signaling", we have compiled a set of assays that are commonly used in many laboratories across the world to assess ligand-induced receptor activation, signaling, and regulation. We have covered cell based assays to record the interaction and activation of heterotrimeric G proteins with activated receptors, generation of second messengers (such as cAMP and Ca++), trafficking of activated receptors by confocal microscopy and direct interaction of GPCRs with arrestins using fractionation approach. We have also included a set of methods to measure G protein activation in vitro, isolation of peptide ligands to monitor their interaction with receptors, and purification of effector proteins (such as arrestin) to use them in direct biophysical studies on GPCRs. Finally, we have highlighted some rapidly evolving in silico approaches to investigate GPCR activation, dimerization, and their interaction with effector proteins